Internal wave activity in the deep Gulf of Mexico - Meunier, Thomas; Le Boyer, Arnaud; Molodtsov, Sergey; Bower, Amy; Furey, Heather; Robbins, Pelle (Frontiers in Marine Science, 2023)
Internal wave activity in the Gulf of Mexico (GoM) is investigated using a fleet of profiling floats. The floats continuously measured temperature and salinity as they drifted at a parking depth of 1500 dbar, allowing for the reconstruction of 2615 time series of isopycnal displacements. Thanks to the dense sampling of the eastern part of the GoM (east of 90°W), the geographical distribution of the internal waves displacement variance and available potential energy (APE) is revealed. The Loop Current (LC) influence region, between the Yucatan shelf to the west and the southern West Florida shelf to the east exhibits increased displacement variance and APE both in the continuum and near-inertial bands, while the north-eastern and central GoM show reduced internal wave activity. As the LC position fluctuates between a retracted and extended mode, we assessed the impact of the presence or absence of the LC in the increased internal wave activity region. It is shown that in the LC influence region, APE is increased (decreased) when the LC is present (absent), suggesting a strong control of the LC on deep internal waves activity. The 1500 dbar flow velocity, bottom roughness, and float altitude also seem to contribute to increased internal waves APE, but their influence is more subtle. Oppositely, no correlation with wind speed or wind intermittency is found.